2017
DOI: 10.1155/2017/6742164
|View full text |Cite
|
Sign up to set email alerts
|

A New Sutureless Illuminated Macular Buckle Designed for Myopic Macular Hole Retinal Detachment

Abstract: Purpose. To report the anatomic and visual results of a new sutureless illuminated macular buckle designed for patients with macular hole retinal detachment related to high myopia (MMHRD). Design. Prospective nonrandomized comparative interventional trial. Methods. Twenty myopic eyes of 20 patients (mean age, 51.4 years; range, 35–65 years) presenting with MMHRD with a posterior staphyloma, in whom the new buckle was used, were evaluated. The buckle used was assembled from a 5 mm wide sponge and a 7 mm wide si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In a previous study, a 25-g self-retaining chandelier endoilluminator along with a wide angle viewing system was used to confirm appropriate indentation. 13 In our case, we achieved satisfactory chorioretinal apposition and closure of MH though with abduction deficit at 3-month follow-up on SD-OCT. We believe that MTM with coexisting pathology can be addressed with scleral wall reshaping using a relatively simple technique of macular buckling with the Morin-Devin T implant.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In a previous study, a 25-g self-retaining chandelier endoilluminator along with a wide angle viewing system was used to confirm appropriate indentation. 13 In our case, we achieved satisfactory chorioretinal apposition and closure of MH though with abduction deficit at 3-month follow-up on SD-OCT. We believe that MTM with coexisting pathology can be addressed with scleral wall reshaping using a relatively simple technique of macular buckling with the Morin-Devin T implant.…”
Section: Discussionsupporting
confidence: 51%
“…12 Many case series with primary EMB or EMB with PPV have reported higher anatomical and functional success rate over primary PPV alone. [6][7][8][9][10][11][12][13] Different macular buckles have been described in the literature. The most popular one is the Ando plombe explant (Ondeko Corporation Japan).…”
Section: Discussionmentioning
confidence: 99%
“…MB is a conventional surgical method for which various types of exoplants and techniques have been developed in recent years, such as the L-shaped and T-shaped silicone sponge that contains titanium, a silicone plate that contains a metal wire, the fibre optic light assisted MB technique and a sterile topical adhesive to fix the buckle. [15][16][17][18] Earlier studies that compared PPV with MB in eyes with highly myopic MHRD showed that MB yielded better anatomic and functional outcomes than PPV. 7 The surgical techniques PPV and ILM peeling were associated with a higher surgical failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…Transillumination of the exoplant under the fovea enables correct positioning of the exoplant. The surgical technique of MB is still progressing and Bedda et al14 suggested using sterile topical adhesive to fix the buckle under the fovea. This could prevent events of scleral perforation or bleeding due to suture placement.…”
Section: Discussionmentioning
confidence: 99%